IMPLEMENTATION OF INVENTORY INFORMATION SYSTEM DESIGN USING ECONOMIC ORDER QUANTITY METHOD - Frieyadie Frieyadie; Tyas Setiyorini (Kresnamedia Publisher, 2021)
The research problems faced are among others the cost of ordering goods which always changes every time there is an order. Poor product order data collection and less than optimal handling of product orders can harm the company. To solve the problem of controlling inventory management, the Economic Order Quantity (EOQ) method is used, which is proven to be effective in overcoming these problems. Contribution is generated by building an inventory management information system so that the problems faced are not repeated. The purpose of this study is to make the cost of ordering goods more stable and more optimal in handling product orders